Studying the Effect of Metallic Precursor Concentration on the Structural, Optical, and Morphological Properties of Zinc Sulfide Thin Films in Photovoltaic Cell Applications. (9th June 2021) - Abel, S.; Leta Tesfaye, J.; Kiran, R.; Deepak, T.; Ruby, A. Usha; Venkatesh, S.; Krishnaraj, R.
Abstract : Thin films of zinc sulfide (ZnS) with different concentrations of zinc acetate have been made by chemical bath deposition technique in acidic medium (pH = 5) on glass substrate using zinc acetate and sodium sulfide as sources of Zn +2 ion and S −2 ion, respectively, and ethylenediaminetetraacetate as complexing agents and sulfuric acid to adjust pH value at a constant deposition temperature of 85°C, and the deposition time of 90 minutes was used. The effect of the concentration of metallic precursor on the structural, morphological, and optical properties of chemical bath deposited zinc sulfide thin films was investigated in this study. The XRD result confirmed mixed phases of crystalline and amorphous structure dominating other phases, which is witnessed by larger crystallite size than other phases. It reveals that the thin films had hexagonal structure at the medium concentration with preferred orientation along (111) plane, and at lower and higher concentration, it showed that film has an amorphous structure in nature. The crystallinity of all the phases significantly enlarged with increasing the zinc precursor concentration. The SEM micrographs showed high-pitched edged irregular-shaped grains covering the substrate with pinholes and bangs. The optical properties investigated by the UV-VIS spectrometer specified a decrease in the optical bandgap of the films between 3.5 eV and 2.6 eV as the zinc acetate concentration in the solution increased from 0.1 to 0.2 M. It showed that the zinc sulfide had high absorption in the UV radiation. The main finding of this paper is that metallic precursor concentration has a significant role in the optical, morphological, and microstructural properties of the cobalt sulfide thin films, which are most suitable for photovoltaic applications.